Extracellular vesicles promote activation of pro-inflammatory cancer-associated fibroblasts in oral cancer - Arebro, Julia; Towle, Rebecca; Lee, Che-Min; Bennewith, Kevin L.; Garnis, Cathie (Frontiers in Cell and Developmental Biology, 2023)
OSCC-derived EVs can activate oral fibroblasts into CAFs that are different from those activated by TGFβ, suggesting different mechanisms of activation and different functional properties. Gene set enrichment analysis showed several upregulated inflammatory pathways in those CAFs exposed to OSCC-derived EVs. Marker genes for inflammatory CAF subtypes were also upregulated, but not in CAFs activated by TGFβ. Finally, cytokine array analysis on secreted proteins revealed elevated levels of several pro-inflammatory cytokines from EVactivated CAFs, for instance IL-8 and CXCL5. Our results reveal the ability of OSCC-derived EVs to activate fibroblasts into CAFs. These CAFs seem to have unique properties, differing from TGFβ-activated CAFs. Gaining an understanding of the interplay between EVs and stromal cells such as CAFs could lead to further insights into OSCC tumorigenesis and potential novel therapeutics.